THE EFFECTS OF THE SWIMMING TRAINING MODEL AIMED AT THE IMPROVEMENT OF FUNCTIONAL ABILITIES - Dragan Krivokapić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
On the sample of 32 fourth grade students of some Belgrade highs schools, who had the physical education classes carried out at the city's swimming pools, an attempt was made to evaluate the effects of the two different programmes of swimming training in different intensity zones, defined relative to the anaerobic threshold. The subjects were divided into two sub-samples of 15 and 17 participants respectively. Before the research began there was no statistically significant difference between them, regarding the observed functional variables. The first training model consisted of swimming at the intensity level within the zone below anaerobic threshold, while the second model involved occasional swimming at a higher intensity sometimes surpassing the anaerobic threshold. The experimental programme with both sub-groups lasted 8 weeks with 3 training sessions per week, 2 of which were identical for both experimental groups, with the third one differing regarding the swimming intensity, this in the first group being still in the zone below, and in the second group occasionally in the zone above the anaerobic threshold. The amount of training and the duration were the same in both programmes. The aim of the research was to evaluate and to compare the effects of the two training models, using as the basic criteria possible changes of the 5 observed functional parameters: morning pulse, absolute and relative oxygen consumption, the heart frequency and the split time in 50 m swimming in the moment of reaching the anaerobic threshold. On the basis of the statistical analysis of the obtained data, it is possible to conclude that in both experimental groups there were statistically significant changes of average values concerning all the physiological variables. Although the difference in the efficiency of the applied experimental programmes is not determined, it can be said that both experimental treatments significantly influenced the improvement of the functional capabilities of the subjects.